Habitat degradation increases interspecific trophic competition between three spiny lobster species in Seychelles. (5th August 2021) - Sabino, Magali A.; Govinden, Rodney; Pethybridge, Heidi; Blamey, Laura; Le Grand, Fabienne; Sardenne, Fany; Rose, Maria; Bustamante, Paco; Bodin, Nathalie
Abstract: Spiny lobsters ( P. penicillatus, P. longipes and P. versicolor ) are heavily dependent on habitats like coral reefs, known to be highly vulnerable to climate change-driven degradation. Yet, little is known about their trophic ecology and their adaptive capacity to a changing environment. In this study, we used fatty acids (FA) analysed in the hepatopancreas and δ 13 C and δ 15 N stable isotopes analysed in the tail muscle of three spiny lobster species from the Seychelles coastal waters to (1) infer habitat use, dietary patterns and potential for resource competition and (2) investigate the effects of reef type and coral bleaching on their trophic niche metrics. We found that there was a potential for interspecific competition between the three species, shown by their high dietary overlap (mean FA niche overlap ranging from 71.2% to 99.5% for P. longipes and P. versicolor in P. penicillatus ) and similar habitat use (δ 13 C value ranges). P. penicillatus, the largest of the three species, was more a generalist than the two other species (i.e., had a larger FA niche) and P. versicolor seemed to feed on smaller/earlier life stage prey than P. longipes (based on differences in δ 15 N values). The potential for resource competition of Seychelles spiny lobsters appeared higher in granite than carbonate reefs, and in post-2016 coral bleaching reefs. Our results suggest that P. penicillatus could have a greater adaptive capacity to climate change due to its higher dietary plasticity and that competition between Seychelles spiny lobsters may increase in the future as the frequency and severity of bleaching events is predicted to increase with climate change. Graphical abstract: Image 1 Highlights: We use trophic niche overlap to identify the potential for resource competition. There is a potential for resource competition between three spiny lobsters species. The largest species had the most diverse diet and the highest δ 15 N values. Potential for competition was higher in the less vulnerable reef habitat type. Potential for competition seemed to increase following a coral bleaching event.